2018
DOI: 10.2147/jpr.s164483
|View full text |Cite
|
Sign up to set email alerts
|

Feasibility and reliability of electrical, mechanical and thermal nociceptive testing and assessment of diffuse noxious inhibitory control in dogs

Abstract: PurposeQuantitative sensory testing has been used to assess the somatosensory system. This study aimed to evaluate the feasibility and reliability of electrical (ENT), mechanical (MNT) and thermal (TNT) nociceptive testing and the effect of a conditioning stimulus on MNT.Patients and methodsSixteen healthy client-owned dogs were included in this study. Stimulation was applied bilaterally to the dorsal and plantar aspect of the metacarpus and metatarsus respectively, using transcutaneous electrical stimulator, … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

1
10
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
3
1

Relationship

2
2

Authors

Journals

citations
Cited by 4 publications
(11 citation statements)
references
References 24 publications
(36 reference statements)
1
10
0
Order By: Relevance
“…These values were significantly different than healthy controls that presented mean positive values for ΔMNT (i.e. inhibitory profile) [10]. This result suggests a dysfunctional DNIC in dogs with NeuP, which is consistent with previous results obtained by different methods of DNIC assessment in dogs suffering from osteoarthritis [17] and osteosarcoma [18] and in rodent models of NeuP [19].…”
Section: Discussionsupporting
confidence: 90%
See 1 more Smart Citation
“…These values were significantly different than healthy controls that presented mean positive values for ΔMNT (i.e. inhibitory profile) [10]. This result suggests a dysfunctional DNIC in dogs with NeuP, which is consistent with previous results obtained by different methods of DNIC assessment in dogs suffering from osteoarthritis [17] and osteosarcoma [18] and in rodent models of NeuP [19].…”
Section: Discussionsupporting
confidence: 90%
“…However, MNT and ENT were not significantly different between the two populations and did not change after treatments in NeuP. This could be explained by the great individual variability of both QST modalities in dogs from different breeds, ages and body weight [10]. On the other hand, a recent study investigating NeuP in Cavalier King Charles Spaniels dogs reported higher MNT after the administration of pregabalin when compared with baseline or placebo treatment [26].…”
Section: Discussionmentioning
confidence: 83%
“…Exclusion criteria were the same as those described below for dogs with NeuP. Data for these individuals were previously reported as part of the validation of our methodology [ 10 ].…”
Section: Methodsmentioning
confidence: 99%
“…Dogs were acclimated to the testing room for 10 minutes before the experimentation and had free access to water. For QST, they were positioned either in semi-sternal position or in lateral recumbency over a mat [ 10 ]. Nociceptive stimulations were stopped as soon as behavioral changes in response to stimuli were observed (looking at the probe, voluntary movement away from the probe, attempts to bite, etc.)…”
Section: Methodsmentioning
confidence: 99%
See 1 more Smart Citation